Total Asset Turnover terhadap Working Capital Pada Perusahaan Perdagangan yang terdaftar Bursa Efek Indonesia - Adi Maulana Rachman; Okto Irianto; Tini Adiatma; Ni Luh Putu Nita Yulianti; Fenty Yoseph Manuhutu; Esy D. Lewaherilla; Nurkholis Syukron (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Abstract. This research was conducted with the aim to know the effect of working capital efficiency and total asset turnover on working capital turnover at sub.sector of big and retail trade which listed in indonesia stock exchange either simultaneously or partially. Population in this study were 59 companies and selectedas many as 17 sub companies large and retail trade sector listed on indonesia stock exchange as a purposive sampling sample. The tool used in this analysis with F test and t test, based on the F test it is know that the significanse value is less than 0.05 ie 0.000. This means that the independent variabel of working capital efficiency and total asset turnover targets simultaneously have a significant effect on working capital turnover. Based on t test is know working capital efficiency and total asse turnover partially significant effect on working capital turnover, because the value is below 0.05 which is 0.000. The method of this study proves that simultaneously and partially free variabel working capital turnover efficiency and total asset turnover have a significant effect on working capital turnover. Keywords: working capital efficiency, Total assets turnover, Working Capital turnover.